2011
DOI: 10.1002/jor.21522
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy in a mouse model of implant‐associated osteomyelitis

Abstract: Implant associated osteomyelitis (OM) is difficult to treat with antibiotics, and outcomes remain poor. Some reports suggest that hyperbaric oxygen treatment is a safe and effective means of treating OM. We tested this hypothesis in a murine model. Clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa, and Klebsiella pneumoniae were used. The mice were infected with each of the three pathogens, treated with 100% oxygen at high pressure, hyperbaric oxygen (HBO), and mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Previously, mouse models of implant-associated osteomyelitis have been limited to intramedullary [9, 20, 24] or trans-cortical pins [17, 25]. These models are beneficial for studying the general etiology of osteomyelitis and biofilm formation [24] or systemic treatment strategies such as various antibiotic regimens [20] and immunization [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, mouse models of implant-associated osteomyelitis have been limited to intramedullary [9, 20, 24] or trans-cortical pins [17, 25]. These models are beneficial for studying the general etiology of osteomyelitis and biofilm formation [24] or systemic treatment strategies such as various antibiotic regimens [20] and immunization [26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Shandley et al used an experimental model similar to ours to test the effect of HBOT (80 min of 100% O 2 at 240 kPa) on bacterial growth in implant-associated OM. The bacterial load (CFU/tibia) of MRSA in infected tibias was significantly higher in HBOT-treated animals, and the authors concluded that HBOT accelerates the growth of S. aureus [20]. It could be hypothesized that HBOT could oxygenate hypoxic biofilms and boost bacterial metabolism, which should lead to higher CFU counts in tibias from animals treated with HBOT compared with no HBOT.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more recent study demonstrated that HBOT could stimulate bacterial growth and thereby accelerate the infection. This was shown by Shandley et al who used a model of implant-associated OM to test the effect of HBOT (100% O 2 at 240 kPa for 80 min) [20]. They found that the bacterial load of Methicillin-resistant Staphylococcus aureus (MRSA) in infected tibias was significantly higher in HBOT-treated animals compared to untreated animals, concluding that HBOT accelerates the growth of S. aureus [20].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the case of osteomyelitis with MRSA infection for example, the effect of HBO is attributed to increased availability of oxygen used by neutrophils for killing microorganisms through oxidative burst [28]. …”
Section: Introductionmentioning
confidence: 99%